PENGARUH REKRUTMEN DAN SELEKSI TERHADAP KINERJA PEGAWAI PADA KANTOR WALIKOTA TANGERANG SELATAN - Hanindya Pratiwi; Yan Kristian Halomoan (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of recruitment and selection on employee performance at the South Tangerang Mayor's Office partially or simultaneously. The method used in this method is a quantitative approach, the existing population of 85 people by taking saturated or overall samples, namely with 85 respondents. The tests used are validity test, reliability test, classical assumption test, linear regression test, correlation coefficient test, determination coefficient test, Hypothesis Test (t test and f test). The results of this study simultaneously have a significant effect on employee performance with regression Y = 0.251 + 0.529 X1 + 0.531 X2 + e, the correlation coefficient value of 0.757 & 0.870 means that simultaneously has a “Very Strong” level of relationship. Where the value is in the interval 0.800 - 1.000. While the coefficient of determination (Adjusted R Square) is 0.751 (75.1%). Based on this value, it shows the percentage between the Recruitment (X1), and Selection (X2) variables affecting Employee Performance (Y) by 75.1% while the remaining (100% - 75.1%) 24.9% is influenced by other variables that are not included. For the hypothesis value, the value of Fcount > Ftabel or (127.992> 3.11). This is also reinforced by sig <0.05 or (0.000 <0.05) thus H0 is rejected and Ha is accepted, this shows that there is a significant effect simultaneously between the Recruitment (X1) and Selection (X2) variables on Employee Performance.